Using conservation behavior to manage ecological traps for a threatened freshwater fish. Issue 8 (13th August 2018) - Hale, Robin; Coleman, Rhys; Sievers, Michael; Brown, Timothy R.; Swearer, Stephen E.
Abstract: Urban stormwater treatment wetlands are constructed to treat stormwater runoff before it enters waterways, but are often inhabited by animals that can suffer impairments. Such effects will be exacerbated if animals mistakenly prefer sites where their fitness is reduced, and are caught in ecological traps. Traps can compromise the persistence of threatened species in urban landscapes, so assessing how animals respond to stormwater wetlands, and whether their fitness varies between stormwater and natural wetlands, can guide management efforts. We examined the habitat selection behavior of dwarf galaxias ( Galaxiella pusilla ), a threatened freshwater fish inhabiting wetlands and streams around Melbourne, Australia. We tested whether fish respond to cues that could indicate habitat quality, and whether they can differentiate between water from stormwater and non‐stormwater wetlands. We also tested whether fitness (e.g., survival, development) was lower at stormwater wetlands. Fish responded weakly to cues and did not avoid stormwater wetlands. Survival was lower at stormwater wetlands, and fish suffered delayed ovarian maturation, potentially due to a lack of food. Thus, stormwater wetlands can be equal‐preference ecological traps for G. pusilla, a key finding with direct implications for conservation. For highly dispersive species that are not selective about habitats, managing ecological traps requires a whole‐of‐landscape approach, with consideration given to where wetlands are constructed. Given the investment required to remediate existing ecological traps, this approach can also identify priority wetlands for intervention. We discuss our results in the context of how insights from animal behavior can inform threatened species conservation in fragmented urban landscapes.